Functional neuroimaging in the acute phase of Takotsubo syndrome: volumetric and functional changes of the right insular cortex - Dichtl, Wolfgang (Clin Res Cardiol, 2020)
BACKGROUND: A brain–heart interaction has been proposed in Takotsubo syndrome (TTS). Structural changes in the limbic system and hypoconnectivity between certain brain areas in the chronic phase of the disease have been reported, but little is known concerning functional neuroimaging in the acute phase. We hypothesized anatomical and functional changes in the central nervous system and investigated whole-brain volumetric and functional connectivity alterations in the acute phase TTS patients compared to controls. METHODS: Anatomical and resting-state functional magnetic resonance imaging were performed in postmenopausal females: thirteen in the acute TTS phase and thirteen healthy controls without evidence of coronary artery disease. Voxel-based morphometry and graph theoretical analysis were applied to identify anatomical and functional differences between patients and controls. RESULTS: Significantly lower gray matter volumes were found in TTS patients in the right middle frontal gyrus (p = 0.004) and right subcallosal cortex (p = 0.009) compared to healthy controls. When lower threshold was applied, volumetric changes were noted in the right insular cortex (p = 0.0113), the right paracingulate cortex (p = 0.012), left amygdala (p = 0.018), left central opercular cortex (p = 0.017), right (p = 0.013) and left thalamus (p = 0.017), and left cerebral cortex (p = 0.017). Graph analysis revealed significantly (p < 0.01) lower functional connectivity in TTS patients compared to healthy controls, particularly in the connections originating from the right insular cortex, temporal lobes, and precuneus. CONCLUSION: In the acute phase of TTS volumetric changes in frontal regions and the central autonomic network (i.e. insula, anterior cingulate cortex, and amygdala) were noted. In particular, the right insula, associated with sympathetic autonomic tone, had both volumetric and functional changes. GRAPHIC ABSTRACT: [Image: see text]